The zonality of ilmenite batteries within the boundaries of the Irshan battle field of the Ukrainian shield - Komliev, О.; Комлєв, О. (Київський національний університет імені Тараса Шевченка, 2023)
World-class titanium and titanium-zirconium placer deposits are located on the territory of Ukraine. They form Ukrainian sub-province of the placer province of Eastern Europe. It also includes the Irshansky placer field for the development of short-lived ilmenite placers. The article presents the results of research of the spatial ratio of placers and root sources, vertical and horizontal zonation of the material composition of placers on 9 detailed sections. This allows us to identify additional criteria for establishing the genesis of placers, which is important when conducting paleogeographic and paleogeomorphological work. The main sources of placers were mainly stratum bodies of various thicknesses, which were independent structures or were elements of the now destroyed domed structures of the foundation. The indigenous bodies and placers in the plan coincide completely, partially, or do not coincide. The criterion of coincidence of root and placer bodies indicates that the useful component from the root bodies to placers moved a distance of several hundred meters. Loose deposits contained in the sediments of the Poltava suite formation of the Late oligocene-Middle miocene age were eluvial, eluvial-deluvial, deluvial, deluvial-alluvial, proluvial and alluvial by genesis. Paleorelief was then favorable for the preservation of placers as the primary concentrations of the useful component of indigenous sources, and their enrichment. Ilmenite placers were then formed on all hypsometric levels of ancient relief, but the most significant of them are at the lower level (in the bottoms and on the slopes of ancient valleys). The results of analyzes of granulometric and chemical composition of monofraction of ilmenite placers, granulometric and material composition of sediment-containing placers, were studied in combination with other data (structural-tectonic, paleogeomorphological).Analyses of the material composition of placers and sediments were selected by interval testing of sections. Based on the results of their processing, quantitative indicators characterizing the particle size distribution and chemical composition of ilmenite were calculated. Their study made it possible to identify different types of sections in the deposits of the contribution of the Poltava suite formation (8 – according to granulometry, 10 – according to the change in the chemical composition of ilmenite), vertical and horizontal zonality, allowing solving various problems (paleogeomorphological reconstructions, to identify consedimentary structures, location detection tectonic inversions).

На території України розташовані титанові і титан-цирконієві розсипні родовища світового рівня. Разом вони утворюють Українську субпровінцію розсипної провінції Східної Європи. Сюди входить і Іршанське розсипне поле розвитку ільменітових розсипів ближнього зносу. У статті наведено результати дослідження просторового співвідношення розсипів і корінних джерел, вертикальної і горизонтальної зональності речовинного складу розсипів на 9 детальних ділянках. Це дозволило виявити додаткові критерії для встановлення генезису розсипів, що важливо для проведення палеогеографічних і палеогеоморфологічних робіт. Корінними джерелами титанових розсипів Іршанського розсипного поля були переважно пластові тіла різної товщини, які представляли самостійні структури або були елементами нині зруйнованих куполоподібних структур фундаменту. Корінні тіла і розсипи в плані збігаються цілком, частково або не збігаються. Критерій збігу коріннихі розсипних тіл указує, що корисний компонент від корінних тіл до розсипних переміщувався на відстань до кількох сотень метрів. Розсипні родовища, що містяться у відкладах полтавської світи пізньоолігоцен-середньоміоценового віку, за генезисом елювіальні, елювіально-делювіальні, делювіальні, делювіально-алювіальні, пролювіальні, алювіальні. Рельєф того часу сприяв збереженню в розсипах концентрацій корисного компонента корінних джерел і їх збагаченню. Ільменітові розсипи формувались на всіх гіпсометричних рівнях давнього рельєфу, але найбільш значні – на нижньому рівні (днища і схили давніх долин). Результати аналізів гранулометричного і хімічного складу розсипів ільменіту, гранулометричного і речовинного складу відкладів, що вміщують розсипи, вивчались з урахуванням структурно-тектонічних, палеогеоморфологічних умов території. Аналізи відбирались методом інтервального опробування розрізів. За результатами їх статистичної обробки вираховувались кількісні показники, які характеризують гранулометричний і хімічний склад ільменіту. Вивчення їх дозволило у відкладах полтавської світи виявити різні типи розрізів (8 – за гранулометрією і 10 – за змінністю хімічного складу ільменіту), вертикальної і горизонтальної зональності. Отримані результати важливі для розвитку геоінформаційного моделювання розсипних родовищ і дозволяють вирішувати традиційні завдання (палеогеоморфологічні реконструкції, вплив палеорельєфу на вміст і якісний склад ільменіту, виявляти давні конседиментаційні структури, місця тектонічних інверсій).
Про зональність ільменітових розсипів Іршанського розсипного поля Української субпровінції розсипної провінції Східної Європи
Keywords: ilmenite; іlmenite placers; root springs; zonation of placers; paleorelief; ільменіт; ільменітові розсипи; корінні джерела; зональність розсипів; палеорельєф